Knocked out by my nunga-nungas : further, further confessions of Georgia Nicolson - Rennison, Louise (New York : HarperTempest, 2002)
The saga of fourteen-year-old Georgia Nicolson continues as she travels to Scotland on a nightmarish family vacation, confesses her anxiety over being the girlfriend of a sex god, and tests the limits of true friendship.
Sequel to: On the bright side, I'm now the girlfriend of a sex god.
650
650
Accelerated Reader AR
Keywords: Interpersonal relations -- Juvenile fiction; Diaries -- Juvenile fiction; Humorous stories; England -- Juvenile fiction